Symposium on prospects for EC-ACP industrial cooperation : introductory speech. - FRIX, Paul (1993)
Discusses the development of EC-ACP industrial cooperation over 30 years and its future prospects. Stresses that in order to relaunch the economic and industrial development of ACP countries, the countries concerned must be aided to (1) develop regional markets, (2) have access to European markets and to those of developed countries, and, (3) develop financial and technical support structures.